Constructivist learning paradigm in the introduction to education subject - IGA Widari; Iwan Jazadi (Intelektual Pustaka Media Utama, 2019)
This study examines the content of constructivist learning paradigms in the textbook and students' understanding of the Introduction to Education course. Data collection methods are the textbook, student answer documentation, focused review session and assignment of student resume. The textbook analysis found five substances of constructivist learning paradigm, namely the nature of human, lifelong education, learning independence, the role of information technology, and the integration of educational benchmarks, which are parts of the textbook chapters. Analysis of the answers to the tasks, quizzes and student exams indicates that the students' understanding of the substance of this material is still medium or partial but has increased significantly after a focused review session was held, i.e. 75% or more students have a good and complete understanding. From the results of this study, it is suggested that (1) the textbook of Introduction to Education is rewritten, to put the five substances of constructivist learning paradigm as separate chapters so as to obtain their broader and deeper study portion; and (2) the materials not yet understood well by the students should be reviewed through a focused review session.